2015
DOI: 10.1038/ejhg.2015.46
|View full text |Cite
|
Sign up to set email alerts
|

SIPA1L3 identified by linkage analysis and whole-exome sequencing as a novel gene for autosomal recessive congenital cataract

Abstract: Congenital cataract (CC) is one of the most important causes for blindness or visual impairment in infancy. A substantial proportion of isolated CCs has monogenic causes. The disease is genetically heterogeneous, and all Mendelian modes of inheritance have been reported. We mapped a locus for isolated CC on 19p13.1-q13.2 in a distantly consanguineous German family with two sisters affected by dense white cataracts. Whole-exome sequencing identified a homozygous nonsense variant c.4489C>T (p.(R1497*)) in SIPA1L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 71 publications
2
23
0
Order By: Relevance
“…It is less clear if the early cataract is a result of the truncated protein being abnormally folded or if the missing domains influence interactions with other critical proteins such as Rap1 or 14-3-3ζ. Evers et al (2015) found that a truncated Sipa1l3, lacking the last 249 amino acids of the C-terminal domain of the SPAR protein, was sufficient to cause cataracts. Future studies will need to establish the specific impact of each domain in eye development and pathways that lead to early cataract formation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is less clear if the early cataract is a result of the truncated protein being abnormally folded or if the missing domains influence interactions with other critical proteins such as Rap1 or 14-3-3ζ. Evers et al (2015) found that a truncated Sipa1l3, lacking the last 249 amino acids of the C-terminal domain of the SPAR protein, was sufficient to cause cataracts. Future studies will need to establish the specific impact of each domain in eye development and pathways that lead to early cataract formation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study employing exome sequencing uncovered a nonsense variant (c.4489C>T; p.R1497*) in Sipa1l3 in siblings with congenital cataract (Evers et al 2015). The peptide encoded by this variant is truncated and contains the Rap-GAP and PDZ domains, but includes only a small fragment of the C-terminal domain of the SPAR protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the SIPA1L3 gene has also been associated with congenital human cataracts (Evers et al, 2015;Greenlees et al, 2015). SIPA1L3 is a member of the signal-induced proliferationassociated [SIPA, also known as the spine-associated rap-gap (SPAR)] proteins.…”
Section: Introductionmentioning
confidence: 99%